PERBEDAAN DISFUNGSI SEKSUAL PADA WANITA PASCA PERSALINAN PERVAGINAM EPISIOTOMI MEDIOLATERAL DAN SEKSIO CAESARIA - Subrata, Roni -; Rahayu, Retno (Universitas Tribhuwana Tunggadewi, 2019)
Postpartum women will experience some changes related to the labor process experienced. Changes that occur are the presence of physical and psychological discomfort. These changes can affect the sexual needs of women and their partners. Causes of Postpartum Female Sexual Dysfunction are dyspareunia, perineal pain, incision wound discomfort including surgery, reduced libido, lack of lubrication in the vagina, changes in body image to negative and anorgasms associated with pain and trauma. The purpose of this study was to determine the differences in sexual dysfunction of women after vaginal delivery with a mediolateral episiotomy with cesarean section at Bangil Pasuruan Hospital. This research using a cross sectional method. The study subjects consisted of vaginal delivery women with mediolateral episiotomy and post cesarean section. Each group consists of 30 people. The sampling technique used was consecutive sampling. After three months postpartum, sexual function is assessed using an FSFI score (Femal Sexual Function Index. Data in the form of a questionnaire then tested by analysis of the T-test. The results of this study a difference between postpartum female sexual dysfunction and mediolateral episiotomy with cesarean section, seen from the desirability of 4,787> 1.67, stimulation 8.723> 1.67 lubrication namely 9,102>1.67 orgasm namely 7,381>1.67 satisfaction is 11,040> 1,67 and pain 9,981> 1,67.